New troglobitic species of Benthana Budde-Lund, 1908 and Benthanoides Lemos de Castro, 1958 from iron-ore caves and their important record in the Amazon biome (Crustacea: Isopoda: Philosciidae) - Cardoso, Giovanna Monticelli; Ferreira, Rodrigo Lopes (Zootaxa, 2023)
A new cave-restricted species of Benthana and two cave-restricted species of Benthanoides are described from iron-ore caves located in the Serra dos Carajás complex, Pará state, in the Amazon biome. Benthana alba n. sp. occurs only in one cave in the south of Serra Norte, in the plateau N5 (cave N5SM2_0077); Benthanoides amazonicus n. sp. occurs in several caves in the north of Serra Norte, in the plateau N1; and Benthanoides tarzan n. sp. occurs in several caves in the Serra do Tarzan. This record represents an important distribution data for Benthana that typically occurs in the Brazilian Atlantic Forest, indicating that such species may represent a relict lineage of this genus. Additionally, efforts must be directed towards the conservation of these species, all of which are associated with caves occurring in areas of intense mining activity.